1977
DOI: 10.2105/ajph.67.10.921
|View full text |Cite
|
Sign up to set email alerts
|

Health beliefs and smoking patterns in heart patients and their wives: a longitudinal study.

Abstract: Smoking patterns of 205 male patients were examined over a period of eight years after a primary myocardial infarction. Smoking data from their wives at one year after the heart attack were also examined. A marked, persistent reduction in smoking was found among the men. Smoking patterns of wives remained essentially unchanged. Smoking patterns before the heart attack were not related to demographic variables, except for the association between smokernonsmoker status and social status measures. Conceptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…It is likely that rates of successful quit attempts would be lower with longer-term follow-up periods, given previous literature demonstrating the difficulty with long-term abstinence. 21 Last, the study was not able to account for potential effects that hospitalization itself may have on preparedness, as patients may be more likely to report being prepared to quit when in the face of a health shock, 22 as well as the fact that some patients may demonstrate a socially desirable response bias influenced by hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that rates of successful quit attempts would be lower with longer-term follow-up periods, given previous literature demonstrating the difficulty with long-term abstinence. 21 Last, the study was not able to account for potential effects that hospitalization itself may have on preparedness, as patients may be more likely to report being prepared to quit when in the face of a health shock, 22 as well as the fact that some patients may demonstrate a socially desirable response bias influenced by hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The trend towards better dialysis session adherence among inpatients in propensity tertile 3 (table 2) supports this hypothesis. Although such behavioral changes are not well-examined in kidney disease, it has been reported that acute myocardial infarction patients may change their smoking habits because of the perception of personal vulnerability that develops following a myocardial infarction [33]. Also, it has been shown that patients who face life-threatening illnesses place higher value on health [34,35], which could potentially lead to changes in health habits.…”
Section: Discussionmentioning
confidence: 99%
“…Weinman et al (2000) found that partner causal attribution regarding lack of exercise was associated with increased-patient exercise at six months post MI. Croog and Richards (1977) found that both patients and their partner's expressed high agreement that smoking was a causal factor in the patient's MI. Patients smoking behaviour significantly declined at one-month post infarction and remained low at seven to eight-year follow-up.…”
Section: Key Findingsmentioning
confidence: 95%
“…Studies have identified significant couple similarity in illness perceptions and particularly among causal attributions (Benyamini, Medalion, & Garfinkel, 2007;Croog & Richards, 1977;Figueiras & Weinman, 2003;Franks, Hong, Pierce, & Ketterer, 2002;Rudy, 1980;Weinman et al, 2000). Some studies have found that concordant illness perceptions may contribute to patient recovery.…”
Section: Key Findingsmentioning
confidence: 99%